The Influence of Digital Advertising and Attractiveness on The Interest of Floating Market MSMEs Actors In Southern Kalimantan - Anas Mahdhori; Anthonius Junianto Karsudjono; Fredy Jayen (Eduvest - Journal of Universal Studies, 2024)
This study aims to analyze the effect of digital advertising and attractiveness on the interest of MSME players in the Floating Market of South Kalimantan. Digital advertising has become a strategic tool in increasing the visibility of MSMEs, especially in the Floating Market which is a local cultural icon. However, the unique traditional appeal of the market remains a dominant factor in maintaining the interest of business actors. This study uses a quantitative approach with multiple linear regression methods to measure the relationship between variables. The results showed that simultaneously, digital advertising and attractiveness have a significant effect on the interest of MSME players. However, partially, only the attractiveness variable has a significant effect, while digital advertising does not show a significant impact. The local cultural attractiveness factor proved to be the dominant variable in motivating entrepreneurs to run their businesses in the South Kalimantan Floating Market.